The Effectiveness of Group Impulse Control Therapy on Coping Strategies and Substance Use Among Individuals With Substance Use Disorders - Rostamfarkhani, Safoura; Abdollahi, Rashin (Mental Health and Lifestyle Journal, 2026)
The present study aimed to investigate the effectiveness of group impulse control therapy on coping strategies and substance use among individuals with substance use disorders. This study employed an applied, quasi-experimental design with a pretest–posttest control group and a follow-up phase. The statistical population consisted of individuals using cannabis who referred in 2024 to the Rah-e Omid Counseling and Addiction Treatment Center. Using convenience sampling, 30 participants were selected and randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received eight sessions of group impulse control therapy based on behavioral chain modification within a cognitive–behavioral framework, while the control group received no intervention during the study period. Data were collected using the Coping Strategies Questionnaire and the Substance Use Tendency Questionnaire. Descriptive statistics were used to summarize the data, and inferential analyses were conducted using multivariate and univariate analysis of covariance (MANCOVA and ANCOVA) to control for pretest effects. All statistical analyses were performed using SPSS version 27, with the significance level set at 0.05. The results of ANCOVA indicated a statistically significant effect of group impulse control therapy on coping strategies after controlling for pretest scores, F(1, 27) = 19.47, p < 0.001, η² = 0.419. In addition, a significant effect of the intervention was found on substance use, F(1, 27) = 102.44, p < 0.001, η² = 0.791, demonstrating a substantial reduction in substance use among participants in the experimental group compared with the control group. Group impulse control therapy is an effective psychological intervention for improving coping strategies and reducing substance use among individuals with substance use disorders and may be considered a valuable component of addiction treatment programs.